AJARAN AGAMA HINDU DALAM SATUA SANG KARNA - I Wayan Sudiarta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Traditional Balinese literary works, especially stories/satua are no stranger to Balinese people, because the author's creations are not only a means of entertainment but more than that, there are teachings that are implied in them, so that literary works are said to have the function of entertaining and providing education to the students. the reader. The story as a work of Balinese literature has a very important role in fostering and developing Balinese art. Through these literary works, artists are inspired to create new creations in various forms of art. Balinese people, especially those who study literature, are still making efforts to preserve these literary works, both written and oral. Stories have very valuable positions and values, especially those related to the teachings of Hinduism. Research on the results of Balinese literary works in the form of stories has been widely carried out, however in reality there are still many stories that have not been studied, so a story of Sang Karna is taken. Satua Bali in its current development seems to have faded in the midst of Balinese society. One of them is Satua Sang Karna, this is inseparable from the development of science and technology which tends to make the younger generation prefer stories that exist in cyberspace. Based on this, it is deemed necessary to conduct research on Satua Sang Karna, the results of which can be donated as a source of scientific information for the community, so that later it can be used as guidelines in life. Keywords: Hindu religious teachings and the story of Sang KarnaSekolah Tinggi